The Financial Industry 4.0 - Ngo, Thanh; Guegan, Dominique; Vo, Dinh-Tri (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We invite you to read the Special Issue on The Financial Industry 4.0. It is a collection of 13 articles published in a Special Issue of International Journal of Financial Studies (MDPI) in 2020-2022. The main emphasis of this reprint is on The Financial Industry 4.0 to provide insightful understanding about the benefits as well as the challenges that financial institutions are facing under the Industry 4.0 era. The articles in this Special Issue discussed the potential of blockchain technology, the impact of fintech on financial inclusion in developing countries, the role of fintech in the insurance industry, and so on. It highlights the benefits of fintech, such as improved efficiency, accuracy, and customer experience, but also notes the challenges and risks involved, such as data privacy and security concerns. Collaboration between financial institutions, regulators, and technology firms is seen as necessary to promote innovation and ensure the stability and security of the financial system while addressing the challenges and risks associated with fintech.